ANTICANCER EFFECTS OF LIGUSTICUM CHUANXIONG HORT ALCOHOL EXTRACTS ON HS766T CELL - Xie, Xu; Tian, Ye; Yin, Shuo; Lin, Yao; Tan, Guang (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
This research was mainly to study the optimisation of extraction process of Ligusticum Chuanxiong Hort alcohol extracts. Stable passage pancreatic cancer HS 766 T cell lines were created by cell culture, and the cell proliferation data were measured by MTT assay. The determination of HS766T cell cycle and apoptosis case was done by PI staining and flow cytometry analysis. The results displayed that Ligusticum Chuanxiong Hort can inhibit the proliferation of pancreatic cancer HS 766 T cells. The cell cycle was blocked in G0/G1 phase, and the cell membrane was damaged on observation with microscope. At the same time, the generation of apoptosis was promoted by reduced intracellular Ca2+ concentration. All in all, the HS 766 T cells could be effectively suppressed by Ligusticum Chuanxiong Hort alcohol extracts.